2014
DOI: 10.1002/ejic.201402295
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐State‐Dependent Properties of an Iron(III) Hydrogenase Mimic

Abstract: A biomimetic mononuclear iron(III) model complex was investigated in detail by density functional theory (DFT) calculations. Structural and energetic criteria were employed to confirm the S = 3/2 intermediate state to be the ground state. The ground state was verified by using both pure and hybrid functionals with different amounts of exact Hartree-Fock exchange. A comprehensive study of the influence of the functional as well as thermodynamic corrections to the energetic ordering of spin states was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 73 publications
4
15
0
Order By: Relevance
“…It is interesting to note that the low-spin complexes always have shorter bond distances from the coordinating atoms to the central ion compared to the high-spin counterparts, especially from the water molecules. This behavior has been shown previously in computation calculations with other ligands [ 44 ].…”
Section: Resultssupporting
confidence: 86%
“…It is interesting to note that the low-spin complexes always have shorter bond distances from the coordinating atoms to the central ion compared to the high-spin counterparts, especially from the water molecules. This behavior has been shown previously in computation calculations with other ligands [ 44 ].…”
Section: Resultssupporting
confidence: 86%
“…In the case of Fe III (d 5 ), intermediate spin ground states are observed mainly for complexes of square pyramidal coordination geometry with few exceptions found in octahedral or square planar complexes in case of suitable ligand environments . Although the electronic and magnetic properties of a number of mononuclear S= 3/2 Fe III complexes have been the subject of detailed experimental studies, the corresponding computational studies are limited to the determination of the spin of their ground states, and, to the best of our knowledge, the present report is the first theoretical consideration of the origin of their magnetic anisotropy ,…”
Section: Methodsmentioning
confidence: 99%
“…(C) Results of the Rd.HMM analysis of the final So CMO2, So CMO1 and At CMO1 homology models shown per subunit. Note that in this kind of analysis a Rd-HMM index value of 0.6 is obtained for structures solved by X-ray crystallography [ 42 ]. The RMSD values given are relative to the bacterial monoxygenase (PDB: 3N0Q) used as template for modeling So CMO2 and were calculated using STAMP [ 43 ] to match equivalent positions in the structures.…”
Section: Resultsmentioning
confidence: 99%
“…Analyzing the three homology models with the Rd.HMM protocol [ 42 ] we found that, out of all sequences in the NCBI-RefSeq database, the So CMO2 amino acid sequence (XP_021849509), the At CMO1 amino acid sequence (NP_194718) and the So CMO1 amino acid sequence (XP_021866412) were the first retrieved when using the So CMO2, At CMO1 and So CMO1 homology models, respectively, indicating that the models indeed can accommodate the respective sequences better than the sequences of any other protein in the NCBI RefSeq database. The results of the validation of the homology models shown in Fig 6C indicate an appropriate backbone for all models, with a Rd.HMM index value just slightly below the value reported for X-ray crystallography determined structures [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation